2019
DOI: 10.3390/e21020111
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Production in Thermodynamics

Abstract: Macroscopic many-body systems always exhibit irreversible behaviors. For example, the gas always tend to fill up the unoccupied area until reaching the new uniform distribution, together with the irreversible entropy increase. However, in principle, the underlying microscopic dynamics of the many-body system, either the (quantum) von Neumann or (classical) Liouville equation, guarantees the entropy of an isolated system does not change with time, which is quite confusing comparing with the macroscopic irrevers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…It was often held [4][5][6][7][8][9][10][11][12] that the relative entropy D[ρ E (t)||ρ eq E ] is negligible for large thermal reservoirs. Based on this assumption, some recent papers even directly identified the entropy production with the mutual information between the system and the environment [6,10]. In this Letter we show, however, that in small open systems driven out of equilibrium the opposite is the case.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was often held [4][5][6][7][8][9][10][11][12] that the relative entropy D[ρ E (t)||ρ eq E ] is negligible for large thermal reservoirs. Based on this assumption, some recent papers even directly identified the entropy production with the mutual information between the system and the environment [6,10]. In this Letter we show, however, that in small open systems driven out of equilibrium the opposite is the case.…”
mentioning
confidence: 99%
“…. This conclusion may be surprising because it was often held [4][5][6][7][8][9][10][11][12] that the term D[ρ E (t)||ρ eq E ] is of the second order to the change of the density matrix of the environment ∆ρ E = ρ E (t) − ρ eq E , and therefore can be neglected for large thermal reservoirs. However, whereas such order-of-magnitude arguments are valid for numbers, they should be applied with care when considering complex, multi-element structures, such as density matrices; this is because a sum of many small contributions can still be significant.…”
mentioning
confidence: 99%
“…It turns out the total correlation approximately exhibits a monotonic increasing behavior, and the increasing curve becomes more and more "smooth" with the increase of the bath size. Thus, the total correlation exhibits a quite similar behavior as the irreversible entropy increase in the standard thermodynamics [16][17][18][19]. In contrast, the whole N-body system always keeps a constant due to the unitary evolution, and the entropy of each single TLS increases and decreases from time to time.…”
Section: Introductionmentioning
confidence: 79%
“…Notice that, in practical observations, indeed the full Nbody state is usually not directly accessible for local measurements, and it is the few-body observables that can be directly measured [5,19,24]. Therefore, here we consider the dynamics of the total correlation entropy of the N-body state ρ(t), that is [12][13][14][15],…”
Section: Population Propagationmentioning
confidence: 99%
“…One natural question to ask is how these two terms contribute to entropy production. It was often held that the relative entropy is negligible for large thermal reservoirs [4][5][6][7][8][9][10][11][12], compared with the MI. However, recently it was found that while entropy production could be time-extensive, the MI is strongly bounded from above by the Araki-Lieb inequality [13], so the entropy production could also predominantly come from the relative entropy that measures the displacement of the environment from equilibrium state ρ E [14].…”
mentioning
confidence: 99%